2023
DOI: 10.1186/s12886-023-02924-2
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of corneal endothelial changes after phacoemulsification in diabetic and non-diabetic patients

Abstract: Background Currently, there is still controversy about the differential changes in corneal endothelium function and morphology after phacoemulsification between Diabetes Mellitus (DM) and non-Diabetes Mellitus (non-DM) patients. In this study, we aimed to evaluate the influence of phacoemulsification on the corneal endothelium in DM and non-DM patients. Methods Databases of PubMed, Embase, Web of Science, and the Cochrane Library were searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Several studies compared central corneal thickness between the diabetic and non-diabetic groups [ 18 ]. Although a number of studies found that diabetic patients had thicker corneas compared to non-diabetic subjects, [ 19 , 20 ] some other studies did not report any difference between the two groups [ 5 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies compared central corneal thickness between the diabetic and non-diabetic groups [ 18 ]. Although a number of studies found that diabetic patients had thicker corneas compared to non-diabetic subjects, [ 19 , 20 ] some other studies did not report any difference between the two groups [ 5 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chronic hyperglycemic state of diabetes can damage many body organs such as the eyes, nerves, kidneys, heart, and blood vessels over time [ 2 ]. Although diabetic retinopathy (DR) is the most serious ocular complication of diabetes and one of the causes of secondary blindness during adulthood, [ 3 ] studies have shown that this disease also leads to changes in the anterior eye segment, especially the cornea [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%